Memahami Strategi Perlawanan Seksualitas Perempuan dalam Film “Yuni” - Bethsheba Graciella Jacinda; Hapsari Dwiningtyas Sulistyani; Amida Yusriana (Interaksi Online, 2023)
Women and men should have equal opportunities to communicate and express their sexualities. However, the reality shows that women’s body and sexuality are still bridled from disciplining rules. “Yuni” is a film that tells the story of a society that still holds a tight disciplining rule over female sexuality. This research aims to understand how sexuality resistance strategy and the logic of sexuality perspective are represented in the film “Yuni”. This research uses representation theory, feminist standpoint theory, Luce Irigaray’s resistance strategy, and elements of sexuality. This is a descriptive qualitative research, under critical paradigm, and uses John Fiske’s semiotics method to analyze data findings. The result of this research found that “Yuni” represented resistance strategies through creating female sexuality, creating female language, and intensifying female sexuality. Through these strategies this research discovers that “Yuni” represented female expression of sexuality as a form of resistance, naturalizing the depiction of the female body, female language as a form of resistance, and resistance to the construction virginity. The perspective dominantly seen in “Yuni” is the female perspective, that appeared as the female director’s position towards the issues discussed in the film. However, this research also found that there is still a usage of the known dominant perspective in the effort of female sexuality resistance through the representation of a lesbian relationship that was formed because of trauma, heteronormative construction, and objectification of the female body.